2010
DOI: 10.1007/s00265-010-0951-y
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition affects sex allocation but not sperm morphology in a flatworm

Abstract: Sperm competition has been shown to be an important evolutionary agent affecting the behaviour, physiology, and morphology of both males and females. One morphological trait that is particularly likely to be affected by sperm competition is sperm size because it is thought to influence the competitiveness of sperm by determining sperm longevity, motility, and/or their ability to displace competing sperm. Most comparative studies across taxa have found a positive relationship between the level of sperm competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 55 publications
1
42
2
Order By: Relevance
“…To document sperm morphology, we recovered worms from squeeze preparations, amputated the tail plate (64), and ruptured it by placing it on a microscope slide in 1-2 μL of liquid and covering it with a coverslip. Fully formed sperm emerged from the ruptured seminal vesicle and were documented (65). Because sperm are sensitive to low osmotic pressure, we added small amounts of diluted seawater for freshwater species to prevent osmotic damage to the sperm (artifacts thereof sometimes are reported as bona fide sperm morphology).…”
Section: Methodsmentioning
confidence: 99%
“…To document sperm morphology, we recovered worms from squeeze preparations, amputated the tail plate (64), and ruptured it by placing it on a microscope slide in 1-2 μL of liquid and covering it with a coverslip. Fully formed sperm emerged from the ruptured seminal vesicle and were documented (65). Because sperm are sensitive to low osmotic pressure, we added small amounts of diluted seawater for freshwater species to prevent osmotic damage to the sperm (artifacts thereof sometimes are reported as bona fide sperm morphology).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the flatworm Macrostomum lignano worms raised in larger social groups have larger testes (Schärer & Ladurner, 2003;Brauer, Schärer & Michiels, 2007), a heightened testicular cell proliferation activity (Schärer et al, 2004), and produce more sperm (Schärer & Vizoso, 2007). Furthermore, given that sperm production in large social groups is higher per unit testis size, other sperm production parameters, such as the speed of spermatogenesis or the size of the produced sperm (but see Janicke & Schärer, 2010), may also vary in response to social conditions (Schärer & Vizoso, 2007).…”
Section: (3) Sperm Production Plasticitymentioning
confidence: 99%
“…In intraspecific studies a recurring pattern is for sperm morphometry to differ substantially among individuals but relatively little within individuals, both in species with separate sexes (Ward, 1998;Morrow & Gage, 2001) and in hermaphrodites (Minoretti & Baur, 2006;Janicke & Schärer, 2010). To elucidate the origin of these patterns comparative analyses in different bird groups have suggested that betweenindividual variation in sperm size is most pronounced in species subject to low levels of sperm competition, probably due to relaxed selection on an optimal sperm morphometry and so too presumably on other aspects of spermatogenesis (Birkhead et al, 2005;Calhim, Immler & Birkhead, 2007;Kleven et al, 2008;Lüpold, Linz & Birkhead, 2009a).…”
Section: (2) Variation and Plasticity In Sperm Morphology Within Speciesmentioning
confidence: 99%
“…Crean and Marshall (Crean and Marshall, 2008) showed that males alter the phenotype of their gametes in response to increases in the risk of sperm competition, and that this gamete plasticity resulted in higher fertilisation success when sperm concentrations were high. Gamete plasticity in response to sperm competition is not Environmentally induced (co)variance in sperm and offspring phenotypes as a source of epigenetic effects Dustin J. Marshall* universal, however: Janicke and Schärer (Janicke and Schärer, 2010) found no evidence for changes in sperm morphology in response to sperm competition in flatworms, despite major changes in sex allocation between treatments. Nevertheless, gamete plasticity in response to sperm competition represents an important source of variation in sperm phenotype in a range of species and therefore a potential source of non-genetic effects.…”
Section: Reviewmentioning
confidence: 99%